DESCRIPTION OF THE DEVELOPMENT AND EVALUATION OF A BRAINSTORMING-BASED WORKSHEET IN ENHANCING STUDENTS' WRITING SKILLS: A DESCRIPTIVE RESEARCH APPROACH - Novri Susanti Suparman; Desi Lupita (STAI Nurul Falah Airmolek, 2020)
This research investigates the development and evaluation of a brainstorming-based worksheet as a pedagogical instrument for enhancing students' writing skills. The study involves 35 students from Indragiri Hulu Regency and utilizes a mixed-methods approach, incorporating quantitative assessments and qualitative interviews. The quantitative data reveal a significant improvement in writing scores, with 77% of students using the worksheet achieving higher scores compared to those who did not. These findings indicate a tangible positive impact on writing skills attributed to the worksheet. Qualitative data obtained through interviews with students shed light on their experiences. The worksheet is described as a transformative tool that provides structure and clarity to the writing process. Students report heightened creativity, improved organization, and greater self-assurance in expressing complex ideas. While some initial challenges were noted, students overcame them to realize the long-term benefits of structured brainstorming. The results suggest that the brainstorming-based worksheet offers a valuable approach to writing instruction, fostering confident, creative, and proficient writers. This research underscores the significance of structured methods in enhancing writing skills, offering implications for pedagogy and the advancement of writing education.